A radial tire airtight layer rubber composition and its mixing method
Patent Information
- Application Number
- CN202611356005.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]此外,传统硬脂酸或脂肪酸类改性碳酸钙主要依赖物理吸附或弱界面作用,在高温密炼和高剪切加工条件下,改性层容易发生迁移或脱附,导致碳酸钙表面重新暴露,分散稳定性和界面结合效果难以长期保持
[0052]本发明采用单宁酸对碳酸钙进行表面改性,使单宁酸分子中的多酚羟基与碳酸钙表面的钙离子形成配位包覆层,再将该单宁酸改性碳酸钙与天然橡胶按特定比例制成母胶,并使天然橡胶全部以母胶形式加入氯化丁基橡胶气密层配方中,由此使单宁酸改性碳酸钙在气密层橡胶组合物中的平均分散,减少填料团聚形成的气体渗透通道,延长气体扩散路径,同时降低填料界面应力集中,最终使气密层获得更低的气体透过率、更高的断裂伸长率、更佳的屈挠裂口性能和老化后屈挠耐久性。
Smart Images

Figure SMS_13 
Figure SMS_21 
Figure SMS_23
Abstract
Description
Technical Field
[0001] This invention relates to the field of tire rubber technology, and more specifically, to a radial tire airtight layer rubber composition and its mixing method. Background Technology
[0002] The airtight layer of a radial tire is a crucial functional layer for maintaining internal air pressure in tubeless tires. Its main function is to reduce the rate at which air permeates from the tire cavity into the carcass and the external environment during tire use, thereby maintaining tire pressure stability, driving safety, and lifespan. Current airtight layer compounds typically use halogenated butyl rubbers such as chlorinated butyl rubber and brominated butyl rubber as the main materials. These rubbers contain isobutylene structures in their molecular chains, resulting in low gas permeability, and are therefore widely used in the airtight layers of tubeless radial tires. However, halogenated butyl rubber is expensive and has a high processing viscosity, making it unsuitable for controlling formulation costs and ensuring compounding stability when used alone in large quantities. Therefore, in actual airtight layer formulations, natural rubber, carbon black, calcium carbonate, softeners, and vulcanization systems are often added to adjust processing performance, mechanical properties, and manufacturing costs.
[0003] Calcium carbonate, as a low-cost and widely available inorganic filler, has been used in rubber products to reduce costs and adjust hardness. However, its application in tire airtight layer compounds is significantly limited. The main reason is that ordinary calcium carbonate contains many polar groups on its surface, exhibiting hydrophilic and oleophobic properties, resulting in poor compatibility with non-polar or weakly polar rubber matrices such as chlorinated butyl rubber and natural rubber. During mixing and vulcanization, untreated calcium carbonate particles are prone to agglomeration, forming interface defects between the agglomerates and the rubber matrix. When gas molecules diffuse in the airtight layer, these interface defects and agglomeration voids easily form localized permeation channels, shortening the gas diffusion path and weakening the barrier properties of the airtight layer. Simultaneously, during repeated tire flexing deformation, stress concentration easily occurs around the calcium carbonate agglomerates, promoting the initiation and propagation of microcracks, leading to accelerated growth of flexural cracks in the airtight layer and affecting the long-term reliability of the tire.
[0004] Chinese invention patent CN103483706B discloses a halogenated butyl rubber airtight layer rubber and its mixing process, wherein the formulation includes halogenated butyl rubber, carbon black, calcium carbonate, silane coupling agent and other components. Although this scheme involves adding calcium carbonate and coupling agent to the airtight layer, calcium carbonate is still mainly used as a conventional filler.
[0005] On the other hand, to improve the dispersibility of calcium carbonate in rubber, Chinese invention patent CN107522909A discloses a method for preparing ultrafine calcium carbonate modified rubber materials. This method uses silane coupling agents and methyl methacrylate to modify calcium carbonate, thereby improving its dispersibility and mechanical properties in natural rubber. However, this type of technology mainly targets natural rubber reinforcing systems, focusing on improving the mechanical properties of ordinary rubber materials, rather than addressing the low gas permeability requirements of chlorinated butyl rubber gas-tight layers. While natural rubber can improve processability and elongation properties for gas-tight layers, its gas barrier properties are weaker than those of chlorinated butyl rubber. If natural rubber is added directly in a conventional manner, or if the amount added and the role of the dispersing carrier are not properly controlled, the gas retention performance of the gas-tight layer may be weakened. Therefore, how to utilize natural rubber to improve processing and deformation compatibility while avoiding its adverse effects on gas tightness is a problem that needs to be solved in the design of gas-tight layer formulations.
[0006] Furthermore, traditional stearic acid or fatty acid-modified calcium carbonate mainly relies on physical adsorption or weak interfacial interactions. Under high-temperature mixing and high-shear processing conditions, the modified layer is prone to migration or desorption, leading to re-exposure of the calcium carbonate surface and making it difficult to maintain dispersion stability and interfacial bonding effects in the long term. Although silane coupling agents can improve the bonding between some inorganic fillers and rubber, their specific binding ability to calcium ions on the calcium carbonate surface is limited. Moreover, in high-filler, low-permeability, and airtight layer systems, it is still difficult to simultaneously achieve filler dispersion, gas barrier properties, flexural crack resistance, and cost control. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a radial tire airtight layer rubber composition and its mixing method, enabling the airtight layer rubber composition to possess low gas permeability, good flexural crack resistance, and stable processability.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A radial tire airtight layer rubber composition, said airtight layer rubber composition is prepared by mixing raw materials comprising the following components based on 100 parts by weight of raw rubber:
[0010] Chlorinated butyl rubber (CIIR) 77.5–89 parts by weight.
[0011] Natural rubber 11-22.5 parts by weight,
[0012] 35-45 parts by weight of carbon black
[0013] Accelerator 1.0-3.0 parts by weight,
[0014] Sulfur 0.2–1.2 parts by weight;
[0015] The natural rubber is entirely derived from tannic acid-modified calcium carbonate / natural rubber masterbatch (hereinafter referred to as...). In the masterbatch, the addition of natural rubber is achieved by adding TA-CaCO3 / NR masterbatch;
[0016] The The masterbatch is made of tannic acid-modified calcium carbonate (hereinafter referred to as...). It is formed by mixing natural rubber in a mass ratio of (18-22):(8-12), wherein the tannic acid-modified calcium carbonate introduced by the masterbatch in the airtight layer rubber composition is 22-45 parts by weight.
[0017] Preferably, the airtight layer rubber composition is prepared by mixing raw materials comprising the following components based on 100 parts by weight of raw rubber:
[0018] Chlorinated butyl rubber 77.5–89 parts by weight,
[0019] Natural rubber 11-22.5 parts by weight,
[0020] 35-45 parts by weight of carbon black
[0021] 2-5 parts by weight of zinc oxide
[0022] 1-2 parts by weight of stearic acid
[0023] Anti-aging agent 1-2 parts by weight,
[0024] Paraffin wax 0.5–1.5 parts by weight,
[0025] 5-12 parts by weight of processing oil
[0026] Accelerator 1.0-3.0 parts by weight,
[0027] Sulfur 0.2 to 1.2 parts by weight.
[0028] Preferably, the tannic acid-modified calcium carbonate has an average dispersed particle size of 0.5–2 μm in the airtight layer rubber composition.
[0029] Preferably, the method for preparing the tannic acid-modified calcium carbonate includes the following steps:
[0030] 1) Weigh tannic acid and calcium carbonate according to the mass ratio;
[0031] 2) Add calcium carbonate to an organic solvent containing 5-15 vol% water, and disperse by ultrasonication to obtain a calcium carbonate suspension;
[0032] 3) Prepare a tannic acid solution by adding tannic acid to an organic solvent containing 5-15 vol% water. Slowly add the tannic acid solution dropwise to a calcium carbonate suspension and sonicate at 60-90°C for 1.5-2.5 hours.
[0033] 4) Filter, wash, and vacuum dry to obtain tannic acid modified calcium carbonate.
[0034] Preferably, the mass ratio of tannic acid to calcium carbonate is (0.1-2.0):40, and more preferably (0.5-1.5):40.
[0035] Preferably, the organic solvent is selected from ethanol, acetone or ethyl acetate.
[0036] Preferably, the calcium carbonate is precipitated calcium carbonate with a particle size of [missing information]. The size is 1–5 μm.
[0037] Preferably, the ultrasonic dispersion time in step (2) is 10 to 20 min.
[0038] Preferably, the ultrasonic power in step (3) is 200-500 W and the ultrasonic frequency is 20-40 kHz.
[0039] Preferably, the vacuum drying temperature in step (4) is 60-80°C and the vacuum drying time is 4-8 hours.
[0040] Preferably, the The preparation method of the masterbatch includes the following steps: Tannic acid-modified calcium carbonate and natural rubber are weighed according to a mass ratio; the tannic acid-modified calcium carbonate is divided into 3 equal parts and then mixed in a mixer 3 times. The mixing temperature is 60–140℃, and the total mixing time is 12–20 min. The mixture is then sheeted out to obtain the final product. Masterbatch.
[0041] Preferably, the mass ratio of tannic acid-modified calcium carbonate to natural rubber is 20:10.
[0042] Preferably, the natural rubber is natural rubber; more preferably, it is smoked sheet rubber, one of the grades RSS1 to RSS3.
[0043] Preferably, the accelerator is selected from accelerator MBTS and accelerator TMTD, wherein accelerator MBTS is 0.8 to 1.5 parts by weight and accelerator TMTD is 0.5 to 1.5 parts by weight.
[0044] Preferably, the antioxidant is selected from antioxidant RD.
[0045] Preferably, the sulfur is selected from 10% oil-extended sulfur.
[0046] Preferably, the carbon black is selected from N660.
[0047] Furthermore, the present invention also provides a method for mixing the aforementioned airtight layer rubber composition, comprising the following steps: 1) Mixing the airtight layer rubber composition: mixing TA-CaCO3 / NR masterbatch with chlorinated butyl rubber and various compounding agents (except sulfur and zinc oxide) in an internal mixer at 120-140°C for 5-8 minutes, discharging the rubber, extruding the sheet, and letting it stand for more than 12 hours. 2) Vulcanizing the airtight layer rubber composition: mixing the above-mentioned compounded rubber with sulfur and zinc oxide in an internal mixer at 90-100°C for 1.5-3 minutes, discharging the rubber, extruding the sheet, and letting it stand for more than 12 hours before vulcanization.
[0048] Preferably, the airtight layer rubber composition is prepared at 160±2°C according to TC. 90 Vulcanization yields an airtight film.
[0049] Preferably, the thickness of the airtight rubber layer is 0.8-3.0 mm.
[0050] Tannic acid The 25 phenolic hydroxyl groups and surface It forms multi-point chelate coordination bonds (bond energy approximately 100–150 kJ / mol), far exceeding the 20–40 kJ / mol of stearic acid physical adsorption, and the modified layer does not detach under high-shear conditions during mixing. The modified layer... The surface changes from hydrophilic (contact angle ~15°) to hydrophobic (contact angle ~65°), significantly improving compatibility with the nonpolar CIIR / NR matrix.
[0051] Masterbatch process enables modification First, a uniform dispersion (average particle size 0.5–2 μm) is formed in NR, and this uniform dispersion is maintained when blended with CIIR. The uniformly dispersed particles generate a "gas labyrinth effect": gas molecules are forced to bypass the particles, significantly extending the effective penetration path and reducing gas permeability. Simultaneously, enhanced interfacial bonding allows for effective stress transfer, inhibiting the initiation and propagation of flexural cracks at the interface, and significantly reducing the crack growth rate. The tannic acid flexible coating improves the deformation compatibility of the filler-rubber pair, reducing premature failure caused by stress concentration, thereby increasing elongation.
[0052] This invention uses tannic acid to modify the surface of calcium carbonate, so that the polyphenolic hydroxyl groups in the tannic acid molecules form a coordination coating layer with the calcium ions on the surface of calcium carbonate. Then, the tannic acid-modified calcium carbonate is mixed with natural rubber in a specific ratio to make a masterbatch. All the natural rubber is added to the chlorinated butyl rubber airtight layer formulation in the form of masterbatch. This makes the tannic acid-modified calcium carbonate evenly dispersed in the airtight layer rubber composition, reduces the gas permeation channels formed by filler agglomeration, prolongs the gas diffusion path, and reduces the stress concentration at the filler interface. Ultimately, the airtight layer obtains lower gas permeability, higher elongation at break, better flexural crack performance, and flexural durability after aging. Detailed Implementation
[0053] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present invention.
[0054] (TA-CaCO3)
[0055] Table 1 formula
[0056]
[0057] Preparation of TA-CaCO3:
[0058] 1) Weigh out the precipitated calcium carbonate Add the calcium carbonate suspension to a mixed solvent of ethanol / water (volume ratio 90:10) and ultrasonically disperse for 15 min to obtain a calcium carbonate suspension.
[0059] 2) Dissolve tannic acid in ethanol, then slowly add it dropwise to the calcium carbonate suspension, and sonicate at 80°C for 2 hours (power 300 W, frequency 40 kHz).
[0060] 3) Filter, wash three times with ethanol, and vacuum dry at 70°C for 6 hours to obtain TA-CaCO3.
[0061]
[0062] Masterbatch formulation: The mass ratio of tannic acid-modified calcium carbonate to natural rubber RSS3 is 20:10.
[0063] The formula obtained from this ratio This batch of masterbatch represents the practical upper limit of stable mixing under internal mixer conditions without the addition of processing oil, ensuring... The masterbatch has good flowability and is uniformly miscible with CIIR; the single masterbatch specification facilitates accurate metering and process management during production.
[0064] Preparation: Plasticize natural rubber in a mixer for 2 minutes at 50 rpm. Divide tannic acid-modified calcium carbonate into three equal parts. Add 1 / 3 of the total amount of tannic acid-modified calcium carbonate and mix for 3 minutes at 50 rpm and 120±5℃. Add another 1 / 3 of the total amount of tannic acid-modified calcium carbonate and mix for 3 minutes at 50 rpm and 120±5℃. Finally, add the remaining 1 / 3 of the total amount of tannic acid-modified calcium carbonate and mix for 4-9 minutes at 50 rpm and 120±5℃. Discharge the rubber, pass it through a two-roll mill 8 times, and sheet it to obtain the desired product. Masterbatch.
[0065] (Airtight layer rubber composition)
[0066] Table 2 Formulations of the airtight layer rubber compositions in examples and comparative examples
[0067]
[0068] Table 3. Examples and comparative examples introduced in each embodiment and comparative example. Precipitated calcium carbonate and tannic acid content
[0069]
[0070] Note: In Comparative Examples 1 and 2, 13 parts of NR were added directly (not in masterbatch form); in Examples 1-5, all NR was derived from… Masterbatch, NR + CIIR = 100 parts by weight.
[0071] Compounding of the airtight layer rubber composition: The masterbatch, chlorinated butyl rubber, and all compounding agents (except sulfur and zinc oxide) are mixed in an internal mixer at 120-140°C for 5-8 minutes, the rubber is discharged, the sheets are extruded, and the mixture is left to stand for more than 12 hours.
[0072] Vulcanization of the airtight layer rubber composition: Mix the above-mentioned compound rubber, sulfur and zinc oxide in an internal mixer at 90-100℃ for 1.5-3 minutes, discharge the rubber, sheet it out, and vulcanize it after standing for more than 12 hours.
[0073] Vulcanization of the airtight layer rubber composition: The airtight layer rubber composition is placed on a flat vulcanizing machine and vulcanized at 160±2℃. The vulcanization time is as follows: Determine the sample (approximately 12–20 min) to obtain a standard sample.
[0074] The performance test metrics are as follows:
[0075] 1) Tensile properties: Tested in accordance with GB / T 528.
[0076] 2) Flexural crack: Test according to the Demattia method (GB / T 13934).
[0077] 3) Gas permeability: Tested in accordance with GB / T 15905.
[0078] 4) Hot air aging: Tested according to GB / T 3512 (100℃×48h).
[0079] Using the performance of Comparative Example 1 as a 100% baseline, the relative values were calculated.
[0080] Table 4 Performance Test Results
[0081]
[0082] Note: The lower the gas permeability and the flexural crack growth rate, the better.
[0083] As shown in Table 3, the overall performance of the embodiments is superior to that of the comparative examples. Among them, Example 2 achieves a better balance between gas permeability, elongation at break, flexural crack growth rate, hardness, and cost, taking into account both performance and cost, and is therefore the recommended embodiment. Example 2 (medium masterbatch content, TA-1) has significantly better overall performance than the comparative example. Compared with Comparative Example 1, the gas permeability is reduced by 16%, the flexural crack growth rate is improved by 24%, the elongation at break is increased by 32%, and the flexural crack growth rate after aging is improved by 30%.
[0084] The foregoing description of embodiments of the present invention, through which those skilled in the art are able to implement or use the present invention, will be readily apparent to those skilled in the art. Various modifications to these embodiments will be readily apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novelty disclosed herein.
Claims
1. A radial tire airtight layer rubber composition, characterized in that, The airtight layer rubber composition is prepared by mixing raw materials comprising the following components based on 100 parts by weight of raw rubber: Chlorinated butyl rubber 77.5–89 parts by weight, Natural rubber 11-22.5 parts by weight, 35-45 parts by weight of carbon black Accelerator 1.0-3.0 parts by weight, Sulfur 0.2–1.2 parts by weight; The natural rubber is all from In masterbatch, the addition of natural rubber is achieved through the addition of... The masterbatch is formed by mixing tannic acid-modified calcium carbonate and natural rubber in a mass ratio of (18-22):(8-12), and the tannic acid-modified calcium carbonate introduced by the masterbatch in the airtight layer rubber composition is 22-45 parts by weight.
2. The radial tire airtight layer rubber composition according to claim 1, characterized in that, The airtight layer rubber composition is prepared by mixing raw materials comprising the following components based on 100 parts by weight of raw rubber: Chlorinated butyl rubber 77.5–89 parts by weight, Natural rubber 11-22.5 parts by weight, 35-45 parts by weight of carbon black 2-5 parts by weight of zinc oxide 1-2 parts by weight of stearic acid Anti-aging agent 1-2 parts by weight, Paraffin wax 0.5–1.5 parts by weight, 5-12 parts by weight of processing oil Accelerator 1.0-3.0 parts by weight, Sulfur 0.2 to 1.2 parts by weight.
3. The radial tire airtight layer rubber composition according to claim 1 or 2, characterized in that, The preparation method of the tannic acid modified calcium carbonate includes the following steps: 1) Weigh tannic acid and calcium carbonate according to the mass ratio; 2) Add calcium carbonate to an organic solvent containing 5-15 vol% water, and disperse by ultrasonication to obtain a calcium carbonate suspension; 3) Prepare a tannic acid solution by adding tannic acid to an organic solvent containing 5-15 vol% water. Slowly add the tannic acid solution dropwise to a calcium carbonate suspension and sonicate at 60-90°C for 1.5-2.5 hours. 4) Filter, wash, and vacuum dry to obtain tannic acid modified calcium carbonate.
4. The radial tire airtight layer rubber composition according to claim 3, characterized in that, The tannic acid and calcium carbonate are in a mass ratio of (0.1-2.0):40, preferably (0.5-1.5):
40.
5. The radial tire airtight layer rubber composition according to claim 3, characterized in that, The organic solvent is selected from ethanol, acetone, or ethyl acetate; And / or, the calcium carbonate is precipitated calcium carbonate, with a particle size of The size is 1–5 μm.
6. The radial tire airtight layer rubber composition according to claim 3, characterized in that, The ultrasonic dispersion time in step (2) is 10–20 min; And / or, the ultrasonic power in step (3) is 200 to 500 W and the ultrasonic frequency is 20 to 40 kHz; And / or, the vacuum drying temperature in step (4) is 60-80°C and the vacuum drying time is 4-8 hours.
7. A radial tire airtight layer rubber composition according to claim 1 or 2, characterized in that, The The preparation method of the masterbatch includes the following steps: Tannic acid-modified calcium carbonate and natural rubber are weighed according to a mass ratio; the tannic acid-modified calcium carbonate is divided into 3 equal parts and then mixed in a mixer 3 times. The mixing temperature is 60–140℃, and the mixing time is 12–20 min. The mixture is then sheeted out to obtain the final product. Masterbatch.
8. A radial tire airtight layer rubber composition according to claim 1 or 2, characterized in that, The mass ratio of tannic acid-modified calcium carbonate to natural rubber is 20:10; And / or, the average dispersed particle size of the tannic acid-modified calcium carbonate in the airtight layer rubber composition is 0.5 to 2 μm.
9. A radial tire airtight layer rubber composition according to claim 1 or 2, characterized in that, The accelerator is selected from accelerator MBTS and accelerator TMTD, wherein accelerator MBTS is 0.8 to 1.5 parts by weight and accelerator TMTD is 0.5 to 1.5 parts by weight. And / or, the antioxidant is selected from antioxidant RD; And / or, the sulfur is selected from 10% oil-extended sulfur; And / or, the carbon black is selected from N660.
10. The method for mixing the airtight layer rubber composition according to claims 1 to 9, characterized in that, Includes the following steps: 1) Mixing of the airtight layer rubber composition: The masterbatch, chlorinated butyl rubber, and all compounding agents (except sulfur and zinc oxide) are mixed in an internal mixer at 120-140°C for 5-8 minutes, the rubber is discharged, the sheets are extruded, and the mixture is left to stand for more than 12 hours. 2) Vulcanization of the airtight layer rubber composition: Mix the above-mentioned compound rubber, sulfur and zinc oxide in an internal mixer at 90-100℃ for 1.5-3 minutes, discharge the rubber, sheet it out, and vulcanize it after standing for more than 12 hours. Preferably, the airtight layer rubber composition is prepared at 160±2°C according to... Vulcanization yields an airtight film; Preferably, the thickness of the airtight rubber layer is 0.8-3.0 mm.
Citation Information
Patent Citations
A halogenated butyl rubber gas-tight layer rubber and its mixing process
CN103483706B
Preparation method of superfine calcium carbonate modified rubber material
CN107522909A